Straightforward Individual Incentive Compatibility in Large Economies - Hammond, Peter J. (Review of Economic Studies, 1979)
Journal Article Straightforward Individual Incentive Compatibility in Large Economies Get access Peter J. Hammond Peter J. Hammond University of Essex Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 2, April 1979, Pages 263–282, https://doi.org/10.2307/2297050 Published: 01 April 1979 Article history Received: 01 December 1976 Accepted: 01 September 1978 Published: 01 April 1979